From problems to performance: a systematic review of problem-based learning in K-12 mathematics - Ayari, Mohamed Arselene; Sellami, Abdellatif; Santhosh, Malavika E.; Naji, Khalid Kamal; Al-Ali, Abdulla; Al-Hazbi, Saleh Mohammad Ali (Frontiers in Education, 2025)
IntroductionThis systematic review investigates the implementation of Problem-Based Learning (PBL) in K-12 mathematics education, offering a recent synthesis of current interventions.MethodsIn line with PRISMA guidelines and predefined inclusion and exclusion criteria, the review shortlisted 40 relevant studies. The analysis focused on four key questions: the types of PBL models and intervention strategies employed, the mathematics topics most frequently addressed, the type of PBL frameworks implemented, and the student outcomes assessed.ResultsFindings reveal that integrated PBL approaches are more common (n = 26) than exclusive PBL models (n = 16), incorporating game-based, ethnomathematics-based, digital-based, STEM-oriented, and project-based interventions. Within PBL interventions, Geometry (n = 15) and Algebra (n = 14) emerged as the most addressed domains, followed by Arithmetic (n = 7) and Applied Mathematics (n = 5). The five-step PBL framework, involving the steps: (1) Orient/Identify, (2) Investigate/Plan, (3) Implement/Solve, (4) Evaluate/Reflect, and (5) Extend/Share, was the most frequently applied model (n = 22). Analysis of investigated student outcomes indicates that PBL interventions support a broad range of cognitive, affective, social, and meta-cognitive outcomes. Problem-solving skills (n = 13) and mathematics achievement (n = 12) were the most assessed, followed by self-efficacy/self-confidence (n = 5) and emotional outcomes (n = 4).DiscussionFor policymakers and educational stakeholders, these findings emphasize the importance of contextually relevant integrated-PBL strategies to enhance student learning outcomes, support student development, and promote active engagement across diverse mathematics topics.